Species contribute differently to the taxonomic, functional, and phylogenetic alpha and beta diversity of freshwater fish communities. Issue 11 (8th July 2014) - Pool, Thomas K.; Grenouillet, Gaël; Villéger, Sébastien; Ricciardi, Anthony
Abstract Aim We examined the current biogeographical patterns of native fish communities throughout France, using a multifaceted taxonomic, functional and phylogenetic diversity approach. We then identified the contribution of individual species to each facet of watershed's native fish diversity. Location Continental France. Methods The taxonomic, functional and phylogenetic diversity of the fish communities were quantified at the watershed‐scale (i.e. alpha diversity approach), and congruencies between diversity facets were assessed. Variation between watersheds was then quantified (i.e. beta diversity approach) using Jaccard's dissimilarity index for all three facets of diversity, and congruencies were assessed. We subsequently determined the relationship between alpha and beta diversity for each diversity facet. Lastly, the mean relative contribution of each species to watershed's alpha taxonomic, functional and phylogenetic diversity was quantified. The conservation status of each species was considered to determine if threatened and endangered species contributed more significantly to watershed alpha diversity than common species. Results Across all watersheds, taxonomic, functional and phylogenetic diversity facets were found to be highly congruent using both the alpha and beta diversity approaches. In contrast, the relationship between the watersheds' alpha and beta diversity was primarily negative; watersheds with decreased beta diversity tended to have increased alpha diversity for all three facets. Individual species also rarely contributed prominently to more than one diversity facet, with conservation status insignificantly influencing species relative contributions. Main conclusions We found that native fish diversity 'hotspots' exist in France; exhibited in our results by areas of high, overlapping taxonomic, functional and phylogenetic diversity. Consequently, conservation planning approaches supported by species‐based metrics may concurrently target areas of increased ecological and evolutionary importance at the watershed‐scale. Interestingly, a diverse mosaic of species accounted for the different facets of diversity, suggesting that future reductions in species richness could have differential effects on each watershed's diversity facets.